Hubungan Sanitasi Lingkungan dan Personal Hygiene dengan Kejadian Kecacingan pada Anak di Wilayah Kerja Puskesmas Kenali Besar - Angel Sitorus; Oka Lesmana; Ashar Nuzulul Putra; Marta Butar Butar (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Worm infestation remains a public health problem among elementary school children, closely related to environmental conditions and clean and healthy living behaviors. This study aims to analyze the relationship between environmental and behavioral factors and the incidence of worm infestation in elementary school children. This study used a case-control design with an observational analytical approach. The study subjects consisted of a case group (children with worm infestation) and a control group (children without worm infestation). Independent variables included the availability of trash cans, clean water availability, handwashing with soap, nail hygiene, and footwear use, while the dependent variable was the incidence of worm infestation. Data were collected through interviews and observations and then analyzed using the Chi-Square test. The analysis showed that several environmental and behavioral factors were significantly associated with the incidence of worm infestation (p < 0.05). This study concluded that environmental sanitation conditions and personal hygiene behaviors play a significant role in the incidence of worm infestation in elementary school children. Therefore, efforts are needed to improve environmental sanitation and educate people about clean and healthy behaviors as a step to prevent worm infections.